Itsbat Nikah Bagi Pasangan Suami Istri yang Menikah Sirri Setelah Berlakunya Kompilasi Hukum Islam (KHI) : Studi di PA Medan Tahun 2016 – 2018 - Mesdi Tanjung; Hasballah Thaib; Utari Maharany Barus; Idha Aprilyana Sembiring (Universitas Sumatera Utara, 2019)
Abstract. Marriage Confirmation is a process of confirming a husband and a wife who have done sirri (unregistered) marriage. Its purpose is to obtain marriage certificate for marriage legitimating according to Article 2, paragraphs 1 and 2 of Law No. 1/1974. Basically, its implementation is intended for certain thing as stipulated in paragraphs 1, 2, and 3 of KHI (Compilation of the Islamic Laws). The research problems were how about 1) the procedure of lodging confirmation of marriage for sirri marriage, 2) judge’s consideration in handing down a verdict on the doers of sirri marriage, and 3) the legal consequence of judge’s verdict on sirri marriage in the Religious Court, Medan. The result of the research shows that the procedure of marriage confirmation is filed to the Religious Court in five steps: registering it to the Religious Court in Medan, giving the court a cash advance for the cost of lawsuit, waiting for summon for the court session, attending the hearing, and court’s verdict. The judge’s consideration in handing down the verdict is 1) in the legal ground of lodging confirmation of marriage to the Medan Religious Court whether the applicants have legal ground as specified in Article 7, paragraph 4 of KHI, 2) evidence and legal fact, 3) testimony of witnesses and evidence in the court session, 4) reasons for lodging marriage confirmation, 5) its benefit, 6) since it is traditional in some communities, and 7) it is found in Article 7, paragraph 3, letter (e) of KHI: a marriage of those who have no marriage prohibition according to Law No. 1/1974. This Article is used by the judge in the Medan Religious Court to accept the marriage confirmation. The legal consequence of the court’s verdict in accepting marriage confirmation for sirri marriage is 1) viewed from legality, viewed from the aspect of lodging the request for marriage confirmation, and 3) viewed from the aspect of legal standing. Keywords: marriage confirmation, judge, religious court